Another breakthrough in cultural preservation; Bali Mandara Nawanatya - I Gede Mas Suputra (Bali Tourism Journal, 2018)
Conservation, as well as cultural development activities, are essential to be conducted to maintain the identity of a nation, moreover preserve its existence. When we discuss about culture, Bali, the island of thousand temples, offers whole package of cultural charms; whether in the form of art, religion, civilization, tools and technology, social organization, knowledge, and language system. In order to preserve these cultural aspects, Provincial government of Bali continues to strive various activities. Bali Mandara nawanatya, an activity proclaimed by the government of Bali province as a medium to cultivate the creativity of Balinese artist, is held throughout the year at Taman Budaya, Art Centre Denpasar. The opening parade of this weekend’s art activities was merrily held with theme Tri Buana Kertih or harmony in three layers of the universe. Participants consisting of students from various schools in Bali as well as local arts groups such as Yayasan Penggak Men Mersi, Kisrama Production-Singaraja, Fortuna Management-Singaraja and art activists from neighbourhood province like Banyuwangi Ethno Carnaval attends the opening parade or referred as the cultural parade of ‘Bali Art Carnaval’. Albeit its applauding carnival, obviously the exhibition that runs throughout the year seems attract less visitor to enjoy the performances. it may be another challenge that require attention not only for Government, but also for society as social support in preserving as well as motivating their culture development